2014
DOI: 10.4236/jct.2014.510100
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Antineoplastons A10 and AS2-1 in Adult Patients with Recurrent Glioblastoma Multiforme: Final Report (Protocol BT-21)

Abstract: Treatment of recurrent glioblastoma multiforme (RGBM) creates one of the most difficult challenges to neuro-oncology. The purpose of this study is to evaluate the outcome of adults with high-grade glioma with special attention to RGBM patients treated with Antineoplastons (ANP) A10 and AS2-1 injections. The study was conducted according to Protocol BT-21, which accrued patients who failed standard radiation therapy (RT) and chemotherapy. There were 40 candidates registered in the study. Among the intent-to-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The additional inclusion, exclusion and removal from the study criteria were the same as in the other brain tumor study [11]. All study subjects and/or guardians read, understood, and signed written informed consent prior to enrollment.…”
Section: Patient Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The additional inclusion, exclusion and removal from the study criteria were the same as in the other brain tumor study [11]. All study subjects and/or guardians read, understood, and signed written informed consent prior to enrollment.…”
Section: Patient Populationmentioning
confidence: 99%
“…The patients were advised to continue the treatment until the maximum response was achieved and for eight months thereafter. The details of administration of ANP were published before [11].…”
Section: Treatment Planmentioning
confidence: 99%
See 1 more Smart Citation
“…ANP A10 capsules contain 500 mg of 3-phenylacetylamino-2,6-piperidinedione, which is metabolized in the body to 4:1 ratio of PG, and isoPG and AS2-1 capsules contain 500 mg of 4:1 ratio of PN and PG [6]. Interim results of the phase II studies have already been reported as well as case reports of long-term survival of HGG and diffuse intrinsic pontine glioma (DIPG) [3,[7][8][9][10][11][12][13][14][15][16]. Here, we discuss a case of very long survival (over 21 years) of PAA with pathologically-confirmed complete response (CR).…”
Section: Introductionmentioning
confidence: 99%
“…A recently published phase II study evaluated the safety and efficacy of ANP A10 and AS2-1 in recurrent high-grade glioma, with special emphasis to RGBM. Objective responses (OR) were determined in 17% of eligible patients, overall survival (OS) was 65.5% at 6 months; 56.7% at 9 months, 39% at 1 year and 4.4% at 2, 5, and 10 years [12].…”
Section: Introductionmentioning
confidence: 99%